A new species of the Vaejovis eusthenura group in Oaxaca, Mexico (Scorpiones: Vaejovidae) - López, Carlos Santibañez; Sissom, W. David (Zootaxa, 2010)
Vaejovis oaxaca, a new species of the Vaejovis eusthenura group is described from the Mexican state of Oaxaca. It is found in lowlands ranging from the Mitla area in central Oaxaca southeast into the Isthmus of Tehuantepec and the eastern edge of Chiapas.